2015
DOI: 10.31901/24566322.2015/09.03.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sense of Meaning in the First-year of Study on Throughput at an Institution of Higher Learning in South Africa

Abstract: Inevitably, life in the twenty-first century globalised world brings people into contact with "others". Through these contacts, the need for interactions demands that these people find different ways of understanding one another to generate knowledge. In order for them to achieve this objective, they need a strong and coherent medium. First additional language education has been developed in South Africa to unravel as well as address challenges posed to competence in intercultural communication, with the empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, few insights have examined the influence of environmental incentives on the consequent learning processes and outcomes from an analytical perspective (Liu et al, 2020). Our results are in accord with previous studies indicating that mental engagement design (Khedher et al, 2019), meaning clues (Makola, 2015), and real‐time accomplishment perception (Imran, 2019) could predict subsequent behavioural routine and learning performance through learning app (Yang et al, 2016). Although existing evidence emphasized learners could collaborate and communicate with each other by the mobile technology, our findings indicated that it is insufficient to merely focus on engaging design and sophisticated social features.…”
Section: Discussionsupporting
confidence: 93%
“…However, few insights have examined the influence of environmental incentives on the consequent learning processes and outcomes from an analytical perspective (Liu et al, 2020). Our results are in accord with previous studies indicating that mental engagement design (Khedher et al, 2019), meaning clues (Makola, 2015), and real‐time accomplishment perception (Imran, 2019) could predict subsequent behavioural routine and learning performance through learning app (Yang et al, 2016). Although existing evidence emphasized learners could collaborate and communicate with each other by the mobile technology, our findings indicated that it is insufficient to merely focus on engaging design and sophisticated social features.…”
Section: Discussionsupporting
confidence: 93%